Student psychology-based optimization-tuned cascaded controller for frequency regulation of a microgrid - Gupta, Sindhura; Mukhopadhyay, Susovan; Banerji, Ambarnath; Sanki, Prasun; Sinha, Pampa; Biswas, Sujit K.; Khan, Baseem; Ali, Ahmed; Bokoro, Pitshou (Frontiers in Energy Research, 2024)
This paper presents a student psychology-based optimization (SPBO)-tuned cascaded control scheme for an interconnected microgrid scenario. Generally, the different distributed energy sources are assembled to form the microgrid architecture, and the majority of the sources are environment-dependent. Furthermore, the intermittent power output from these sources causes a generation–load power mismatch, resulting in power and frequency oscillations. In this regard, the proposed student psychology-based optimization-tuned cascaded controller tackles the power-frequency mismatch issues under an interconnected microgrid scenario. Additionally, an improved power tie-line model is introduced considering the effect of line resistance in the microgrid scenario, as line resistance plays a significant role in power flow between the control areas. In addition, numerous case studies are investigated to examine the effectiveness of the proposed design methodology under the suggested control scheme. Furthermore, a detailed performance analysis is carried out considering the proposed model operation under a 12-node radial distribution network in order to examine the system compatibility in a practical distribution network. The obtained results ensure superior performances in terms of the system’s overall peak over/undershoots, oscillations, and settling time utilizing the proposed controller under the improved microgrid scenario.